Vasectomy effect on canine seminal plasma biochemical components and their correlation with seminal parameters - Souza, Fabiana Ferreira de [UNESP]; Mello Martins, Maria Isabel; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2006)
Three semen samples were collected at 48 It intervals from 20 mature research dogs previously conditioned to manual semen collection. Vasectomy was performed in all dogs, and 15 days after surgery, another three ejaculates were similarly collected. The semen was evaluated, and centrifuged to obtain seminal plasma for measurement of pH, and concentrations of total proteins (TP), total chlorides (Cl), calcium (Ca), potassium (K), and sodium (Na). The seminal plasma protein profile was evaluated by SDS-PAGE; molecular weights and the integrated optical density (IOD) of each band were estimated. There was a negative correlation between K concentration and progressive motility (r = -0.49, P = 0.027), sperm vigor (r = -0.60, P = 0.0053), and plasma integrity, evaluated by both the hypo-osmotic swelling test (r = -0.50, P = 0.026) and a fluorescent stain (r = -0.45, P = 0.046). Positive correlations between Na and K pre- and post-vasectomy (r = 0.88, P < 0.001; r = 0.56, P < 0.01, respectively) were verified. There were a total of 37 bands pre-vasectomy and 35 post-vasectomy (range, 100.6-3.6 kDa). Bands B9 and B13 (42.6 and 29.2 kDa) were not present post-vasectomy. The IOD of band B3 (73.5 kDa) was higher (P 0.03) pre-vasectomy, compared to post-vasectomy; conversely, the IODs of bands B29 and B37 (7.8 and 3.6 kDa) increased (P 0.026 and 0.047). Pre-vasectomy, there was a positive correlation (r = 0.49, P = 0.029) between band B37 band (3.6 kDa) and the Na:K ratio. In conclusion, K appeared to be involved in sperm motility in dogs and could be a tool to evaluate sperm function. The prostate contributed several elements to canine seminal plasma. Vasectomy changed Ca concentrations and the protein profile of the seminal plasma. Further studies must be performed to clarify the function of these elements on the in vivo fertility of dogs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: electrolyte; seminal plasma; electrophoresis; vasectomy; canine